Edukasi Kompres Hangat Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif di PMB Pera Simalingkar B Medan Tuntungan Tahun 2023 - Imran Saputra Surbakti; Kamelia Sinaga; Rumondang Sitorus; Asnita Sinaga; Agustina Tumanggor; Rosmani Sinaga (jurnal ABDIMAS Indonesia, 2023)
Warm water compresses given to a woman's lower back in the area where the fetal head presses on the spine will reduce pain, heat will increase circulation to the area thereby correcting tissue anoxia caused by pressure. This study aims to determine the effect of warm compresses on reducing labor pain during the first active phase. This type of research is Quasi experiment, which is research that is used to determine whether or not there are consequences of "something" imposed on the subject being studied by looking for the effect of certain treatments on others under controlled conditions. A sample is a portion taken from all objects studied and is considered to represent the entire population. The sample in this study was 20 people in one intervention group. The sampling technique was Purposive Sampling, namely taking samples according to the criteria determined by the researcher. Data collection techniques use questionnaire sheets and respondent observation sheets. The data analysis technique uses the Independent T test. Statistical testing uses parametric analysis with the significance of the test results determined based on the p value <0.05. Based on the statistical test results, it is known that the p value is 0.001<0.05 which means that there is an influence on the intensity of pain before and after administration. Warm Compress. This research means that there is a significant relationship between the effect of warm compresses on reducing labor pain during the first active phase at PMB Pera Simalingkar B Medan Tuntungan in 2023